A Systemic Functional Linguistics Analysis of Cohesion and Coherence in Written Nursing Care Reports - Kailani, Ahmad (International Journal of Educational Best Practices, 2017)
This study analyses 25 nursing care reports written by nursing students majoring in the International Class of Nursing Diploma at a higher education institution in Indonesia. The main research focus is to assess the cohesion and coherence of nursing care reports in relation to their grades. The Systemic Functional Linguistics framework, with a focus on the textual metafunction, serves as a tool for analyzing cohesion, Thematic structures and Thematic development of the texts. The analysis of text cohesion revealed that all texts predominantly used lexical cohesion and reference to build internal ties within the texts. Reiteration of the same lexical items throughout the texts and heavy use of personal pronouns indicated the exploitation of these systems. In terms of coherence via Thematic structure, it was found that textual Themes were predominantly used. All the texts relied heavily on unmarked Themes, with no evidence indicating a proportional use of marked and unmarked Themes. In terms of Thematic development, Theme reiteration was the main method of text development for all texts. However, a few instances of Zig-zag Thematic development were found in texts in the higher graded categories. None of the texts used multiple Rheme patterns as an alternative method of text development.